2019
DOI: 10.1039/c9ra06843k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of novel dithioacetal–naphthalene derivatives as potential activators for plant resistance induction

Abstract: In this paper, a series of novel dithioacetal–naphthalenes were designed and synthesized for plant immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The former was synthesized by the esterification of phenylpyruvic acid using methyl chloride and DBU [ 37 ]. The latter was afforded by a substitution reaction between 4-hydroxybenzaldehyde and 1-(chloromethyl)naphthalene, in the presence of oven-dried K 2 CO 3 [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The former was synthesized by the esterification of phenylpyruvic acid using methyl chloride and DBU [ 37 ]. The latter was afforded by a substitution reaction between 4-hydroxybenzaldehyde and 1-(chloromethyl)naphthalene, in the presence of oven-dried K 2 CO 3 [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Phytotoxic activities against tobacco and anti-TMV activity were assessed according to the aforementioned method (Ji et al, 2019;Wang et al, 2012). Tobacco mosaic virus (TMV) was purified.…”
Section: Evaluation Of Phytotoxic Activities Against Tobacco and Anti...mentioning
confidence: 99%
“…The results indicated that compound 116 (Figure 35) exhibited the best activity against PVY in vivo, with the EC 50 value of protection activity of 122 μg/mL, which was distinctively better than Ribavirin and Ningnanmycin. Ji et al [118] reported a series of novel dithioacetalnaphthalenes and evaluated for their in vivo antiviral activities against TMV and CMV. The results indicated that most compounds exhibited better activity against CMV than against TMV.…”
Section: Antiviral Activitymentioning
confidence: 99%